Gastroenteropancreatic neuroendocrine tumours – an overview - Maciejewski, Karol; Buchalska, Barbara; Solnik, Małgorzata; Fudalej, Marta; Deptała, Andrzej; Badowska-Kozakiewicz, Anna (Medical Studies/Studia Medyczne, 2022)
Neuroendocrine neoplasms (NENs) belong to a group of various tumours that can arise on many internal organs. Among NENs a large class of gastroenteropancreatic neuroendocrine tumours (GEP-NETs) can be distinguished, which comprise neoplasms arising from the gastrointestinal tract and pancreas. Therefore, this review provides the current status of the World Health Organization classification of GEP-NETs as well as an overview of their clinical presentation, diagnosis, and treatment methods. GEP-NETs are generally divided into 5 groups: pancreatic NETs (PanNETs), gastric NETs (G-NETs), duodenal NETs (D-NETs), jejunoileal NETs (Je-Ile NETs), and neuroendocrine neoplasms of the large intestine. Moreover, in each group several subtypes have been introduced according to cell differentiation, mitotic rate, and Ki-67 index. Low- and intermediate-grade GEP-NETs are well differentiated, have a mitotic rate under 20, and a Ki-67 index under 20%. High-grade GEP-NETs, however, are characterized by poor differentiation, mitotic rate over 20, and Ki-67 index over 20%.